La historia infausta de la inmigración española en Chile a través de los conflictos comerciales y políticos - Estrada Turra, Baldomero (Historia, 2002)
In Chile, European migration did not occur on the massive scale observed in American countries on the Atlantic coast. The migrants in our country did not resolve the need for cheap manpower as they did in other places. The majority of migrants arrived in Chile in a spontaneous way, without any contribution from the government. Spaniards formed the most numerous community of Europeans at the beginning of the twentieth century and they kept this status through the years. We know normally, about those immigrants that have had a successful experience as migrants, that means people that come to Chile as a young poor boys and finally they become rich men. But, we want to study the situation of all those immigrants that had to affront adversity and discover some of the problems that they had suffered as foreigners in our country.